2015
DOI: 10.1186/s40645-015-0052-7
|View full text |Cite
|
Sign up to set email alerts
|

Water and magmas: insights about the water solution mechanisms in alkali silicate melts from infrared, Raman, and 29Si solid-state NMR spectroscopies

Abstract: Degassing of water during the ascent of hydrous magma in a volcanic edifice produces dramatic changes in the magma density and viscosity. This can profoundly affect the dynamics of volcanic eruptions. The water exsolution history, in turn, is driven by the water solubility and solution mechanisms in the silicate melt. Previous studies pointed to dissolved water in silicate glasses and melts existing as molecules (H 2 O mol species) and hydroxyl groups, OH. These latter OH groups commonly are considered bonded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 74 publications
5
30
0
Order By: Relevance
“…H 2 O mol reacts mostly with bridging oxygens to form T-OH bonds (T = Al, Si), so that water solution in silicate melts results in depolymerization of their structure [Scholze, 1960;Mysen et al, 1980;Stolper, 1982;Mysen and Virgo, 1986;Kohn et al, 1989;Zotov and Keppler, 1998;Mysen and Cody, 2005;Xue and Kanzaki, 2006;Mysen, 2007;Malfait and Xue, 2010]. In addition, the formation of M-OH species (with M a metal cation, e.g., Na or Ca) has been documented in silicate and aluminosilicate glasses [Xue and Kanzaki, 2004;Mysen and Cody, 2005;Mookherjee et al, 2008;Le Losq et al, 2015b]. Such species may play an important role in determining the effect of water on melt polymerization, because the reaction of water molecules with metal cations does not lead to melt depolymerization [Xue and Kanzaki, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…H 2 O mol reacts mostly with bridging oxygens to form T-OH bonds (T = Al, Si), so that water solution in silicate melts results in depolymerization of their structure [Scholze, 1960;Mysen et al, 1980;Stolper, 1982;Mysen and Virgo, 1986;Kohn et al, 1989;Zotov and Keppler, 1998;Mysen and Cody, 2005;Xue and Kanzaki, 2006;Mysen, 2007;Malfait and Xue, 2010]. In addition, the formation of M-OH species (with M a metal cation, e.g., Na or Ca) has been documented in silicate and aluminosilicate glasses [Xue and Kanzaki, 2004;Mysen and Cody, 2005;Mookherjee et al, 2008;Le Losq et al, 2015b]. Such species may play an important role in determining the effect of water on melt polymerization, because the reaction of water molecules with metal cations does not lead to melt depolymerization [Xue and Kanzaki, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…In reaction (2), O ,௧ could be a bridging oxygen (i.e., an oxygen bridging two tetrahedrally coordinated, network-forming cations), a non-bridging oxygen in an aluminosilicate tetrahedron, or a "free" oxygen; and OH ௧ represents a hydroxyl group bonded to an aluminosilicate polymer (Behrens and Nowak 1997;Kohn 2000) or an alkali or alkaline-earth cation (Le Losq et al 2015). Combining reactions (1) and (2) ↔ 2OH ௧ , which is governed by an equilibrium constant ‫ܭ‬ (Stolper 1982a) that can be approximated by…”
Section: Speciation Of Water In Silicate Meltsmentioning
confidence: 99%
“…2) 29 Si NMR frequency as well as that observed for Si Q 4 (Al0) is most likely due to variation in Si-O-Si bond angle. For example, (Le Losq et al 2015) showed that lithium, sodium, and potassium tetrasilicate glasses, there is a systematic shift in Si-O-Si bond angles in Q4 species, where from Li + to K + the bond angles decreased.…”
Section: Resultsmentioning
confidence: 99%